Applied English Listening Strategy on Vocational High School Students of Accounting Department - Arisman, Rizal (Universitas Ahmad Dahlan, 2024)
This research came with the problem of the type and level of the metacognitive, cognitive, and socio-affective listening strategy used by the eleventh-grade students at SMK Negeri 1 Baubau during the listening comprehension session of the English subject. These strategies were important for developing language skills and understanding in various contexts. They could be consciously taught and practiced to improve listening comprehension and communication skills. This research aimed to determine the type and level of metacognitive, cognitive, and socio-affective listening strategy used by the eleventh-grade students at SMK Negeri 1 Baubau during the listening comprehension session of English subject. This research applied a descriptive method to reveal the findings related to the listening strategies. Sixty-seven eleventh-grade students of SMP Negeri 1 Baubau were involved as the research sample. The result found that the students applied three types of listening strategies: metacognitive, cognitive, and socio-affective strategy, in which the metacognitive and the socio-affective were more highly used than the cognitive strategy. Furthermore, those three types of listening strategies obtained high levels of utilization. Accordingly, it was concluded that the students frequently used all strategies in learning English listening comprehension. Summarily, it was expected that by the high use of listening strategy, they were able to be contained in the instruction activity of listening comprehension to promote the students’ learning comprehension achievement.